Predictors of Failed Extubation in Mechanically Ventilated Children: Single Center Experience - Sally Kamal Ishak; Asmaa Salah Mohamed; Seham Awad El-Sherbini; Basant Salah Saied; Elshimaa Salah Ahmed (Cairo University, Faculty of Medicine, Department of Pediatrics, 2023)
Background: Extubation failure is failure to maintain normal spontaneous breathing after a period of mechanical ventilation with the need for reintubation within 24-72 hours. It has multiple risk factors such as deconditioned muscles, upper airway edema and others. Aim of the Work: To study the frequency and causes of extubation failure in mechanically ventilated children. Patients and Methods: This is an observational prospective study that included all admitted children in Pediatric Intensive Care Unit (PICU), Cairo University Children Hospital who underwent mechanical ventilation (MV) through ETT for more than 48 hours (145 child) with Glasgow coma scale above 8. They were subdivided into successfully extubated (78 children) and failed extubation (67 children). Results: The mean ± SD age of the cohort was 13.5 ± 15.15 months (range1.3-48, median= 8 months). Of them 80 (55.17%) were males, and 65 (44.8%) were females. The commonest underlying diagnosis was pneumonia in 38 (26.2%), bronchial asthma in 32 (22%), encephalopathy in 32 (22%), and aspiration in 11 (7.58%). Failed extubation was encountered in 67 (46.2%) children. The encountered risk factors of extubation failure were: sedation in 12 (16.7%) (p=0.001), excessive tracheal secretion of more than 200 ml /24 h in 14 (18.7%) (p=0.03), accidental extubation in 27 (40.3%) (p=0.01) and the need for higher setting on MV in all 67 children with failed extubation. Among failed extubated patients, the mean± SD for PIP, PEEP, and FiO2 were 14.5± 1.8 /cm H2O, 5.5± 0.5/cm H2O, and 27.5± 6.1% respectively. While, PIP, PEEP, and FiO2 in the successfully extubated group were 12.8± 1.6 /cm H2O, 4.1± 0.4/cm H2O, and 24.8± 5.3%, (p= 0.01, p=0.001 and p= 0.001) respectively. Patients who underwent gradual withdrawal of ventilatory support had a higher frequency of successful extubation than those extubated accidentally (p= 0.01). Sensitivity, and specificity of above mentioned indices for successful extubation were 53.79%, and 28.72% respectively. Conclusion: Causes of extubation failure are the need for long duration of sedation, excessive tracheal secretion, and need for high setting on MV. Furthermore, gradual weaning decreases the frequency of extubation failure. There is a need for a more sensitive and specific comprehensive objective indicator(s) for successful timely extubation.